Conjoncture économique et marchés financiers : rétrospective et perspectives - Sirard, André (Assurances, 1991)
In his overview of the current economic juncture and financial markets in recent quarters, the author first examines the world situation and then takes a look at Western economies: Japan, Germany, France, United States and Canada. The Canadian economy has been in a recession since the second quarter of 1990, and a turnaround is unlikely before mid-1991. The factors examined include the GNP, employment, construction, corporate investment spending, foreign trade, inflation, monetary policy and prices.